PENYULUHAN 4R (REDUCE, REUSE, RECYCLE, REPLACE) DAN KEGUNAAN BANK SAMPAH SEBAGAI LANGKAH MENCIPTAKAN LINGKUNGAN YANG BERSIH DAN EKONOMIS DI DESA MOJOWUKU KAB. GRESIK - Imah Luluk Kusminah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Waste is an unused or disposed material from a source of human activity and natural processes. So far, waste is still a big problem, because there is no proper solution that causes adverse impact on the environment and health. Less of knowledge about waste processing makes people less concerned about the impact caused. All of the time, waste processingby Landfill method where the waste is transported to landfill (TPA) or taken by scavengers and the rest burned or dumped for a long time. The solution is not an appropriate alternative, because landfills are unsustainable and cause environmental problems. Waste that should be an additional income even burned and impacted for health and the environment. With the garbage bank and the principle of 4R (Reduce, Reuse, Recycle, Replace) for solution of waste, it will help the society to make use of waste into additional income.Thatis one of the steps to awaken the public about the awareness of the surrounding environment and create a clean and economical environment.Keywords: waste, waste solution, garbage bank, 4R, Reduce, Reuse, Recycle, Replace